(untitled) (Research, Society and Development, 2020)
Objective: identify strategies that contribute to the promotion of mental health of patients undergoing cancer treatment. Methodology: this is a qualitative research, whose analysis was based on the technique of integrative literature review, carried out with articles published and indexed in the Virtual Health Library (VHL) and in the MEDLINE, LILACS and BDENF databases. Results: of the 331 articles found, after applying the inclusion and exclusion criteria and analyzing their contents, 9 were selected for analysis of the study. Two nuclei of meaning were identified: mental health promotion strategies for cancer patients and humanized nursing care. Conclusion: the strategies for promoting mental health are fundamental in coping with the disease, as they alleviate suffering and contribute to better patient acceptance and therapeutic involvement. However, it also highlights the importance of nursing for the recovery of the individual, and the nurse must have specialized knowledge, therapeutic knowledge of Thanatology and palliative care.